IDENTIFICATION AND TOXICITY TEST OF PHOTOSYNTHETIC PIGMENTS EXTRACTED FROM Caulerpa racemosa USING THE ULTRASOUND ASSISTED EXTRACTION (UAE) METHOD - RIONG S. PANJAITAN; ANGELINA F. SITURU; CINDY M. N. SILAEN (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2023)
Caulerpa racemosa is a green macroalga, also known as sea grapes, which has various bioactive compounds such as pigments. The aim is to isolate pigments of Caulerpa racemosa collected at Senapan Island, West Papua Province, Indonesia, and assay their toxicity against Artemia salina Leach larvae. Pigments were isolated from Caulerpa racemosa using the Ultrasound Assisted Extraction (UAE) method with a mixture solvent, namely acetone-methanol (7 : 3; v/v). In addition, the pigment extract was identified using Thin Layer Chromatography (TLC). The pigment spots were also separated using column chromatography and characterized using UVVis spectrophotometry at 400 – 800 nm. Furthermore, these pigments were tested for their toxicity using the Brine Shrimp Lethality Test (BSLT) method. This result showed six pigment spots in the TLC analysis. Moreover, the major pigments of Caulerpa racemosa were identified using column chromatography and UV-Vis spectrophotometry as pheophytin a, chlorophyll a, and β-carotene. Moreover, chlorophyll-a and β-саrоtеnе pigment have no toxic towards Artemia salina Leach according to BSLT method with LC50 is > 1000 ppm. This study provides the pigments composition of Caulerpa racemosa and their toxicity where is no toxicity activity given.